The Underdetection of Cognitive Impairment in Nursing Homes in the Dublin area: The Need for on-going Cognitive Assessment - WALSH, CATHAL DOMINIC; DIAZ-PONCE, ANA; CAHILL, SUZANNE; COEN, ROBERT (Oxford University Press, 2010)
Sampling of NHs: All general private and voluntary NHs belonging to the former Irish Health Service Executive East Coast Area (Dublin Mid-Leinster) were sampled. Three areas, namely 1, (Dun Laoire), 2 (Dublin South East) and 10 (Wicklow) which represent the former East Coast Eastern Regional Health Authority provided the sampling frame. Four of the 53 NHs were randomly selected. The chance of a NH being sampled was directly proportional to its size. Sampling of residents: The total capacity of the four NHs was 187 beds, and at the time of study, 174 beds were occupied. A sample of 100 residents was randomly drawn, 25 from each NH. Over-sampling occurred at each facility to allow for refusals (please see Appendix 1 in the supplementary data available on the journal website at http://www.ageing.oxfordjournals.org). Only 18 residents or their next of kin refused participation. The MMSE was administered to all 100 residents. Ethical considerations: Ethical approval was granted by Trinity College Dublin. Informed consent was obtained in all NHs, and proxy consent got for those residents known to lack capacity. Instruments: The MMSE was used to assess CI [14]. When used for screening purposes, a cut score of 23/24 is conventionally used for detection of significant impairment. In contrast when the intention is to classify CI severity as was the case in this study, Folstein et al. recommendations were followed, i.e. normal cognitive function = 27?30, mild CI (MCI) = 21?26, moderate CI = 11?20 and severe CI = 0?10. Residents who scored within the normal ranges (MMSE ? 27) were re-assessed using the Montreal Cognitive Assessment (MoCA). The MoCA test is a screening instrument for the detection of mild CI. It was developed to discriminate individuals between mild CI and normal cognitive function [15]. The MoCA test scores 0?30 points. Scores of 26 or above are considered normal. Where residents were classified on the MMSE as severely impaired (MMSE ? 10), a proxy appraisal (the Dementia Screening Scale, DSS) was completed [The DSS total score varies between 0 and 14 with higher scores indicating worse CI [8]]. Using a Likert scale (no impairment, mild, moderate and severe), Directors of Nursing (DONs) perception of resident's cognitive status was also assessed.
PUBLISHED
Keywords: Health care sciences and services; Dementia